O princípio da igualdade e a extinção de punibilidade nos crimes contra a ordem tributária: o arrependimento posterior como escusa absolutória - Ramos, Orlando Mauriz (2018)
The Principle of Equality should be used in all situations involving legal relationships. With the advent of Law no. 9249/95, and consequently with the possibility of extinguishing punishment of authors of crimes against the tax order, after the effective payment of the helpless taxes, some controversies arose regarding the coercive effectiveness of Criminal Law. However, it is observed a differentiated treatment of non-taxable offenders, hence the importance of analyzing the instituting of punishment and acquittals in another perspective. Given that the Brazilian prison population is large, mainly due to practices of crimes against the patrimony, it is searched with the present work, to analyze the fact of the equal application of the benefit given to the authors of the crimes against the tax order, also to the authors of other crimes, who may repent of the criminal practice, restoring the injured object or, in its impossibility, repairing, in a certain way, the damage caused. Equal treatment is proposed between offenders, observing the possibility of extinguishing punishment, with an eye towards reducing new criminal practices, as well as reducing the prison population, generating a possibility of saving for the state, since it will not be obliged to costing the maintenance of the prisoners, a benefit for the victim, since they will be compensated for the damage caused by the practice of the crime, and a possibility of a second chance for the perpetrator, who will not be incarcerated. The analysis was based on bibliographical research, having as sources the doctrine, technical productions and jurisprudences. At first, the importance of taxes was analyzed for the maintenance of state activities, conceptualizing and extracting the purpose of the taxes, in order to understand the need to classify crimes against the tax order, and consequent application of a penalty to the offender. In a second moment, it is sought to understand the beneficent institutes of the Later Regret (Later Repentance) and the Acquittal Excuse (Excusive Absence). And then, the possibility of equal treatment and possible benefits, with the application of the abovementioned institutes, against the State, the victim and the aggressor was evaluated.